Intervención fisioterapéutica en paciente masculino de 62 años con espondilitis anquilosante. - Baque Cabrera, Genesis Lizbeth (2024)
This study focuses on a 62-year-old male patient diagnosed with axial ankylosing spondylitis, a chronic inflammatory disease that affects the spine and limits mobility. The physiotherapy intervention was designed to improve your quality of life and reduce associated pain. Throughout the study, a treatment plan was implemented that included specific exercises and therapeutic modalities. The results reflected significant improvements in mobility, pain reduction, and patient quality of life. This case highlights the importance of physical therapy as an essential component in the management of ankylosing spondylitis and provides recommendations for future physical therapy treatments in patients with this condition.